The relationship between impulsivity, affect and a history of psychological adversity: a cognitive-affective neuroscience approach - Ipser, Jonathan (Department of Psychiatry and Mental Health, 2015)
There is increasing evidence that trauma exposure is associated with impulsive behaviour and difficulties regulating affect. The findings of recent studies implicate the disruption of neurobiological mechanisms, particularly those involving the neurotransmitter serotonin, in both impulsivity and affect regulation.